Urban legibility condition in Nigeria: A narration of residents' experience in Ibadan metropolitan area - Oluwaseun Ayodele Olowoporoku; Oluwole Daramola; Kamilu Olaniyi; Gbenga Odeyemi; David Mobolaji (Economic and Environmental Studies (E&ES), 2019)
Peoples' opinion has been an adjudged tool for proffering solution to various urban problems. By this, information is sourced to guide policy-makers and other environmentally concerned stakeholders in taking enlightened decisions about the future of cities. This study therefore examined urban legibility across different residential zones of Ibadan metropolis with a view to providing information that could enhance the livability of the city and others with similar background. A total of 327 residents were selected for the survey using systematic sampling technique. The study revealed that the most predominant urban legibility elements used in navigation in the core and transition zones were areas names while availability of nearby churches was the prominent urban legibility elements in giving/receiving directions in the suburban. The study revealed that variation existed in the importance residents attached to the various urban legibility elements as well as the effectiveness of these elements across the various residential areas of the metropolis. Furthermore, the study established that locating places in Ibadan in terms of describing and taking description is a challenging task. It recommended that the government should work out modalities to locate all urban legibility elements, enlighten the public on the need to incorporate these elements in order to improve street coordinate system in the study area and also develop and implement existing development plan with the integration of urban legibility elements.
Keywords: R10; R14; R52; R53; 330; urban legibility; urban centres; residential areas; descriptions; metropolis; Ibadan